PENERAPAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA KOMPETENSI MEMBACA ALQURAN - Heriadi Heriadi (Bajang Institute, 2022)
The learning process to provide more optimal results, appropriate learning methods are needed; effective, efficient, and fun. Peer tutor learning method is expected to be an alternative. To find out the effectiveness of peer tutoring learning methods in increasing students' interest, motivation, and learning outcomes, especially in the competence of reading the Alquran. The researcher conducted research on students in class XI IPA SMA Negeri 3 Sidrap in the form of classroom action research and carried out in three cycles. The results of the study prove that in order to improve the quality of learning Islamic Education requires innovation and appropriate, effective, efficient, and fun learning strategies. Learning with peer tutoring methods is one alternative in an effort to improve the model and learning method of Islamic Education, especially in the competence of reading the Alquran of students. Learning and treatment is considered successful if the process and learning outcomes have increased by 50% or more from the initial conditions and complete learning reaches 100%.